Bout some methodological approaches in the study of representative democracyin Kyrgyzstan (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
In the presented article, the theoretical basis was the work of both classics and modern authors, in which institutions of representation were analyzed conceptually or in the context of socio-political phenomena. The methodological basis was the general scientific principles of systemic and structural-functional analysis in combination with a specific historical and comparative approach, which made it possible to study the genesis and current state of the institutional environment of representative democracy in its relationship with other phenomena of the socio-political sphere. Comparative analysis was used to identify distinctive characteristics in the implementation of reforms in Kyrgyzstan after gaining independence. The systems approach allows us to project the institutions of representative democracy, which was due to the identification of cause-and-effect relationships between various institutions within the political system (form of government and method of government formation, form of government and representative system, party and electoral systems). The structural-functional method was used to identify the normative structure of institutional formations. A theoretically meaningful analysis of existing theories, concepts of institutions of representation, as well as the development of generalizing methodologies, synthesis of basic scientific approaches contributed to the development of final conclusions that will be useful in the practical work of government bodies in Kyrgyzstan.
Keywords: representative authorities, democratic institutions, theory, concept, essence, specificity